Comparison of concentrations of immunoglobulins (IgA, IgM, IgG) in blood serum in patients with suppurative otitis media - حسن يارا; مصطفى ابراهيم; فيصل رضوان (Latakia University Journal -Medical Sciences Series, 2024)
The research aimed to determine whether the serum levels of immunoglobulins IgA, IgG, and IgM are important in distinguishing between acute and chronic suppurative otitis media by: studying the serum levels of immunoglobulins (IgA, IgM, IgG) in patients and comparing them. The results showed a statistically significant difference in the serum levels of immunoglobulin IgG (higher in chronic inflammation than in acute inflammation). There was also a statistically significant difference in the serum levels of immunoglobulin IgM (higher in acute inflammation than in chronic inflammation). There was no statistically significant difference in the serum levels of immunoglobulin IgA in acute and chronic inflammation.